Ophiostoma ulmi DNA naturally introgressed into an isolate of Ophiostoma novo-ulmi is clustered around pathogenicity and mating type loci - Et-Touil, Abdelali; Dusabenyagasani, Mathieu; Bouvet, Guillaume; Brasier, Clive; Bernier, Louis (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ), 2019)
The invasive fungal pathogens Ophiostoma ulmi and O. novo-ulmi have caused two successive pandemics of Dutch elm disease since the beginning of the 20th century. In nature, the highly aggressive O. novo-ulmi may hybridize with the less aggressive O. ulmi. Growth rate and molecular analyses were conducted on an unusual, moderately aggressive O. novo-ulmi isolate, AST27, carrying an introgressed pathogenicity gene, Pat1-m; on highly aggressive O. novo-ulmi isolate H327; on O. ulmi isolates Q412T and W9; and on progeny from laboratory crosses between H327 and AST27. Genetic analysis indicated that the Pat1 and Mat1 (mating type) loci were in different linkage groups corresponding to O. novo-ulmi H327 chromosomes 1 and 2, respectively. Most of the molecular differences between the nuclear genomes of H327 and AST27 occurred in the vicinity of Pat1 and Mat1. In addition, two putative quanti-tative trait loci, Mgr1 and Mgr2, which influence mycelial growth rate at 21°C and 28°C, the optima for O. novo-ulmi and O. ulmi, were linked to Mat1 and Pat1, respectively.